Tako-Tsubo Cardiomyopathy in a 92-Year Old Woman - Mariana S. Parahuleva; Mathias Grebe; Christiane Neuhof; Harald Tillmanns; Ali Erdogan (Clinical Medicine Insights: Case Reports, 2011)
Tako-Tsubo cardiomyopathy (TTC) is an acute reversible cause of segmental myocardial dysfunction that is poorly understood and cannot be explained by the occlusion of a single coronary vessel. Its clinical presentation is similar to that of acute coronary syndrome and is often precipitated by a severe psychological or physical stress.